Autobiographical Memory, Gratitude, Forgiveness and Sense of Humor: An Intervention in Older Adults - Chamorro-Garrido, Alberto; Ramírez-Fernández, Encarnación; Ortega-Martínez, Ana Raquel (Frontiers in Psychology, 2021)
Research has shown that happiness and well-being play a fundamental role in the health of older adults. For this reason, programs based on Positive Psychology seek to improve quality of life, preventing and reducing the appearance of emotional disorders. The objective of this study was to verify whether an intervention based on Autobiographical Memory, Forgiveness, Gratitude and Sense of humor would increase quality of life in institutionalized older adults. We used a quasi-experimental design with pre- and post-intervention measures, and follow-on measures at 3, 6 and 12 months. A total of 111 institutionalized older adults participated in the study and were randomly assigned to one of three groups: experimental (n=36), placebo (n=39) and control (n= 36). Measurements were taken of depression, subjective happiness, satisfaction with life, psychological well-being and specific memories. Program duration was eleven weeks, followed by refresher sessions of the activities that had been conducted. The results showed that the intervention was effective, producing lasting increase in the participating adults’ well-being, maintained for the following 12 months, in contrast to the other two groups. In conclusion, the proposed intervention proved to be a novel tool that was effective, easily applied, and able to improve quality of life and emotional disorders in older adults.